Transforming Student Competencies in Emancipated Learning: Entrepreneurship-Based Curriculum Design - Trihantoyo, Syunu; Purwono, Rudi; Herachwati, Nuri; Roesminingsih, Erny; Andari, Shelly; Paramboor, Jafar (Universitas Negeri Malang, 2023)
ABSTRACT: Changes in the fulfillment of student competencies in the study program are increasingly massive. Universities are required to be able to be more adaptive and flexible in responding to any changes quickly as well as the ability to detect changes that occur early. This study aims to analyse the transformation of student competencies based on the entrepreneurship curriculum which is discussed in the context of independent learning. The method used in this study was a literature review of 133 articles published in Scopus-indexed journals. This research also used the background of the education management study program at the State University of Surabaya. The results of the study found that to realize the entrepreneurship curriculum in the study program, several aspects are needed, namely: managerial, organizational, 21st-century skills, and the learning process.Keywords: student competence, independent learning, entrepreneurship-based curriculum